Manajemen Pengelolaan Usaha Mahasiswa Program Studi Pendidikan Ekonomi FKIP Universitas Sriwijaya - Yuliana FH; Deskoni Deskoni; Firmansyah Firmansyah (Universitas Nusantara PGRI Kediri, 2024)
Students' interest in entrepreneurship shows a positive trend, but what is no less important in running a business is not only the courage to start but also the consistency needed from students to be able to maintain the existence of their business through regular and directed business management. This research aims to 1) provide a general overview of student businesses and 2) how business management is carried out by students of the Sriwijaya University Economic Education Study Program Class of 2018-2020 in terms of operational and product management, capital, and financial management, and marketing management. This type of research is qualitative descriptive research with data collection techniques using in-depth interviews, observations and documentation of 20 students who run businesses. Based on the results of research that has been obtained data that there are 13.5% of students who run businesses in the fields of services, reseller, art / crafts, and culinary. In managing its business on operational and product management, most of it is still done independently because the focus is still divided between lectures and managing business. In addition, the limitation of capital is one of the obstacles in starting a business and for financial management management that is still very simple by making records related to cash in and outflow funds to find out the amount of business profit. Furthermore, marketing management is done through offline and online marketing through social media and marketplaces.